Karakterisasi Bakteri Tanah Penghasil Enzim Hidrolitik yang Diisolasi dari Pulau Muna, Sulawesi Tenggara, Indonesia: Characterization of Hydrolytic Enzyme Producing-Bacteria Isolated from Soil of Muna Island, Southeast Sulawesi, Indonesia - Wibowo, Muhammad Arya; Priyanto, Jepri Agung; Budiarti, Sri (Jurnal Sumberdaya Hayati, 2024)
Soil bacteria are considered a promising source of extracellular enzymes, such as amylase, cellulase, and protease. In this study, 15 bacterial strains isolated from the soil of Muna Island, Southeast Sulawesi, Indonesia, were preliminary screened for amylolytic, cellulolytic, and proteolytic activities. The present study aimed to characterize cellular morphology, determine hemolytic characteristics, and to screen amylolytic, proteolytic, and cellulolytic activities of bacterial strains isolated from the soil of Muna Island. Based on the Gram staining procedure, 15 bacterial strains exhibited diverse cellular morphologies. Ten out of 15 strains belonged to Gram-positive bacilli, while the others belonged to Gram-negative bacteria (bacilli or cocci). Four strains, encoded as M7, P4, P5, and P7, were hemolytic negative. These potential strains exhibited different capabilities in producing extracellular enzymes. The four strains were capable of producing protease, while amylase and cellulase were only produced by two strains (M7 and P7). These strains have good prospects for further study and development for industrial and biotechnological applications.